Muscle Dysfunction and Functional Status in COVID-19 Patients during Illness and after Hospital Discharge - Psenicka, Otakar; Brutvan, Tomas; Kratky, Jan; Krizova, Jarmila (Biomedicines, 2024)
BACKGROUND: COVID-19 pneumonia is associated with SIRS and hypercatabolism. The aim of this study was to determine muscle loss during the acute phase of COVID-19 pneumonia and evaluate long-term sequelae in discharged patients. METHODS: A total of 16 patients with COVID-19 pneumonia and respiratory insufficiency were included in the study. Selected parameters (weight, BMI, LBM = lean body mass, albumin, CRP, NLR = neutrophil-to-lymphocyte ratio, ultrasound measured thickness of rectus femoris muscle = US RF and rectus femoris + vastus intermedius = US RF + VI, handgrip strength, quality of life = EQ-5D questionnaire, and activities of daily living = Barthel's ADLs) were recorded on admission, discharge, and 1, 3, and 6 months after discharge. RESULTS: The most significant changes were between hospital admission and discharge: US RF and RF + VI (-1.28 ± 1.97 mm, p = 0.046; -1.76 ± 2.94 mm, p = 0.05), EQ-5D score (14.6 ± 19.2, p = 0.02), and ADLs (17.1 ± 22.6; p = 0.02). There was a significant positive correlation between US RF + VI and handgrip strength (p = 0.014) and a negative correlation between weight and Barthel index (p = 0.012). There was an association between muscle function with an EQ-5D score and ADLs during outpatient check-ups, most noticeably between handgrip strength, US RF+VI, and ADLs (p = 0.08; p = 0.1, respectively). Conclusions: In patients with COVID-19 pneumonia, there is a significant reduction of health-related quality of life, impaired even 6 months after hospital discharge, influenced mainly by muscle loss. During the hospital stay, there was a significant muscle mass reduction. Ultrasound measurement of thigh muscle thickness may be a useful method to monitor muscle loss.
Keywords: critical illness; quality of life; muscle ultrasound; COVID-19; long-term outcomes